Essential clinical anesthesia / edited by Charles A. Vacanti [and four others] - Vacanti, Charles A.; Sikka, Pankaj K.; Urman, Richard D.; Dershwitz, Mark; Segal, B. Scott (Cambridge medicine., 2011)
"The clinical practice of anesthesia has undergone many advances in the past few years, making this the perfect time for a new state-of-the-art anesthesia textbook for practitioners and trainees. The goal of Essential Clinical Anesthesia is to provide a modern, clinically focused textbook giving rapid access to comprehensive, succinct knowledge from experts in the field. All clinical topics of relevance to anesthesiology are organized into 29 sections consisting of more than 180 chapters. The print version contains 166 chapters that cover all of the essential clinical topics, while an additional 17 chapters on subjects of interest to the more advanced practitioner can be freely accessed at www.cambridge.org/vacanti. Newer techniques such as ultrasound nerve blocks, robotic surgery, and transesophageal echocardiography are included, and numerous illustrations and tables assist the reader in rapidly assimilating key information. This authoritative text is edited by distinguished Harvard Medical School faculty, with contributors from many of the leading academic anesthesiology departments in the United States and an introduction from Dr. S. R. Mallampati. Essential Clinical Anesthesia is your essential companion when preparing for board review and recertification exams and in your daily clinical practice"--Provided by publisher.